The Structural Adjustment Process and Agricultural Change in Pakistan in the 1980s and 1990s (The Distinguishedl Lecture) (The Pakistan Development Review, 1994)
Pakistan has gone through many eventful political and economic changes since the late 1970s. Some of them have been transient, but many were deep and structural, hence even irreversible. Their consequences have been both promising and disturbing. The political system, since at least the mid-1980s, has been gradually democratised, but it is by no means stabilised as the events of 1993 clearly indicate. The economy has grown and transformed, but its management has been erratic. Many of the changes in the economy have come with the growth of the informal sector, both visible and invisible (illicit), which remains unaccounted for in the official statistics. In several urban and rural areas, persuasive though mainly anecdotal evidence suggests that the average standard of living far exceeds the impressions one gets from the national income accounts, household income and expenditure surveys. The growth of rent-seeking in the public and private sectors, illicit trade in drugs and smuggling across borders, informal activities in the rural and urban areas, and evasion of taxes have all contributed to the growth of the economy and distribution of assets and income.